A Taxonomic Study of Phytoplankton in the Basin of the Great Al- Faw Port and the Estuary of the Shatt Al-Arab - Al-Waeli (Iraqi Journal of Aquaculture, 2025)
The study aimed to know the qualitative estimate of the phytoplankton community in the Great Al-Faw Port Basin, and to compare it with the phytoplankton present in the Shatt Al-Arab estuary considering it a newly formed geographical area. This study is the first in this area, this was done by identifying three sites for collecting samples, two sites within the Grand Al-Faw Port Basin, which are the western breakwater, which represents the first site, the Eastern breakwater, which represents the second site, and the Shatt al-Arab Estuary, which represents the third site, samples were collected seasonally from 2022. Additionally, some environmental factors were measured, which may be related to the spread and distribution of phytoplankton, the temperature were between 14.7-32 ˚C, salinity 39.6-41.6 PSU, pH 7.83-8.5, dissolved oxygen 5.5-8.4mg/l, turbidity 4.36-64.9 NTU, phosphate 0.4-0.9mg/l, nitrate 0.6-1.97mg/l, chlorophyll-a- 6.2-21.73mg/m3 and TDS 46.1-53.77ppm. The study identified 64 taxonomic unit (genera and species) from phytoplankton belonging to 5 Divisions of the three sites. The relative diversity index of genera showed, that Bacillariophyta was the most dominant compared to others, with 40 taxonomic unit (62.5%), followed by Dinophyta with 21 taxonomic unit (32.8%), Then Chlorophyta, Ochrophyta and Haptophyta the study recorded one species for each of them ( 1.5 %).